Caracterização da fertilidade atual dos solos da região de Guarapuava-PR - Ribas, Cilton (2010)
For many years, liming and fertilization techniques were adopted to increase soil fertility and crop yields at Guarapuava’s Region, South of Paraná State. Therefore, from the upper soil layers, there was a modification on the availability of nutrients on the soils, which were originally acid and leached, transforming the region into a great cereal producer. The objectives of this study were to establish the actual scenery of the fertility of the soils on Guarapuava’s Region, majorly managed under no till system (NT), as well as to identify fertility problems and propose new study focus on the area, aiming to achieve better soil chemical conditions and enhanced plant nutrition and crop yield. From a 9.500 set of soil test results from 12 cities on Guarapuava’s microregion, 6.534 referring to the 0,0 – 0,2 m depth, with collection date ranging on the 2007-2009 period, were selected, setting up a solid and up-to-date data bank with soil chemical indicator for the region. Through “descriptive statistics” procedures of the SPSS (Statistical Package for the Social Sciences) software, individual profiles of each chemical indicator present at soil test results were traced, with mean and frequency distribution for each city and for de regions as a whole. It was observed that the soils of the Region, clayey in texture, presented organic matter content compatible to the high cation exchang capacity (CTCpH 7,0) found, low acidity and low aluminum level, phosphorus deficiency and high magnesium level in relation to calcium and mainly in relation to potassium. Therefore, management practices leading to enhance phosphorus and potassium and to control magnesium soil levels may contribute to improve plant nutrition and maximize crop yields. As proposition, it is suggested that focus is given to the study on interactions between lime and gypsum, that can be phosphorus source besides of calcium and sulfur, along with phosphorus and potassium sources, searching for better basic cations balance and phosphorus availability on soils, with emphasis on the role of crop rotation under NT with species that are efficient to recycle these two nutrients.